Resources and constraints in linguistic identity performance: a theory of authorship - Grant, Tim; MacLeod, Nicci (Language and Law / Linguagem e Direito, 2018)
The majority of practicing forensic linguists working on questions of authorship subscribe in some form to a theory of linguistic identity that relies on a view of language as essentially a product of sociolinguistic experiences and membership of particular identity categories. On the other hand, discourse analysts tend to adopt a social interactionist view, seeing language as a resource to be drawn on for the performance of particular identities. In order to bridge this gap we set out our theory of identity which acknowledges the importance of pioneering works such as Johnstone (1996) and Bucholtz and Hall (2004) who theorise identity as being interactionally emergent, while simultaneously allowing space for certain aspects of identity to persist across different interactional moments. Within the context of deceptive identity performances by undercover police officers in online investigations against child sex abusers, we propose a model for understanding the relationship between language and identity that is neither essentialist nor radically interactionist. Such a model can support the work of the forensic linguist in their endeavours to train officers in identity assumption tasks, and explicates a particular phenomenon we have observed in their attempts, namely identity ‘leakage’.